Analisis Pengelolaan dan Pelestarian Cagar Budaya sebagai Wujud Penyelenggaraan Urusan Wajib Pemerintahan Daerah (Studi pada Pengelolaan dan Pelestarian Situs Majapahit Kecamatan Trowulan Kabupaten Mojokerto) - Rosyadi, Khalid (Jurnal Administrasi Publik, 2014)
Abstract: Local Government Affairs is divided into compulsory and optional. One of compulsory is cultural affairs which includes the management and preservation of Trowulan Majapahit Site. However, in practice they often overlap in these matters, it is also due to the Trowulan Majapahit Site as national heritage which is also the authority of the central government in Kemendikbud (Ministry of Education and Cultural) Environment, Directorate of Culture. This study aims to analyze the management and preservation of Trowulan Majapahit Site as a compulsory affairs of Local Government, Mojokerto Regency, and the actors involved in it. This study used a qualitative descriptive study. Management of Trowulan Majahit Site based on five regulations as a legal basic, but there is no specific regulation governing this case. On the budget side, budgets already shared from the State Budget, Provincial Budget and District Budget. While, in its preservation has been performed rescue, security, zoning, maintenance, and restoration, but also not optimal cause of constrained to lack of resources and budgets. The main actors involved are Disporabudpar (The Official of Youth, Sport, Cultural, and Tourism) Â Mojokerto and BPCB (House of Preservation of Cultural Heritage) Mojokerto. Keywords: Management and Preservation, Trowulan Majapahit Site, Compulsory, Local GovernmentÂ Abstrak: Urusan Pemerintahan daerah terbagi atas urusan wajib dan pilihan. Salah satu urusan wajib tersebut adalah urusan kebudayaan yang di dalamnya termasuk pengelolaan dan pelestarian situs Majapahit Trowulan. Namun, dalam pelaksanaannya masih sering terjadi tumpang tindih dalam urusan ini, hal ini juga dikarenakan Situs Majapahit Trowulan sebagai Cagar Budaya Nasional yang juga merupakan wewenang Pemerintah Pusat di Lingkungan Kemendikbud, Ditjen Kebudayaan. Penelitian ini bertujuan untuk menganalisa pengelolaan dan pelestarian Situs Majapahit Trowulan sebagai urusan wajib Pemerintahan Daerah Kabupaten Mojokerto, serta aktor-aktor yang terlibat di dalamnya. Penelitian ini menggunakan penelitian deskriptif kualitatif. Pengelolaan Situs Majapahit Trowulan berdasarkan pada lima regulasi sebagai payung hukumnya, namun belum ada regulasi khusus yang mengatur hal ini. Di sisi anggaran sudah terdapat sharing anggaran yang bersumber dari APBN, ABPD Provinsi dan Kabupaten. Sedangkan, dalam pelestariannya telah dilakukan penyelamatan, pengamanan, zonasi, pemeliharaan, dan pemugaran, namun juga belum optimal karena terkendala kurangnya sumber daya dan anggaran. Aktor utama yang terlibat adalah Disporabudpar Kabupaten Mojokerto dan BPCB Mojokerto.Kata Kunci: Pengelolaan dan Pelestarian, Situs Majapahit Trowulan, Urusan Wajib, Pemerintahan Daerah